Interventricular fibroma. Echocardiographic diagnosis and successful surgical removal in infancy. Issue 6 (December 1983) - Reece, I J; Houston, A B; Pollock, J C
Abstract : A 7 month old infant underwent successful surgical removal of a huge interventricular septal fibroma. We believe this to be the youngest child to have undergone successful removal of such a lesion.